2018
DOI: 10.1017/s0007123418000200
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle to Peace? Ethnic Geography and Effectiveness of Peacekeeping

Abstract: Under what conditions does peacekeeping reduce one-sided violence in civil wars? This article argues that local sources of violence, particularly ethnic geography, affect peacekeeping effectiveness. Existing studies focus on the features of individual missions, yet curbing one-sided violence also depends on peacekeepers’ capacity to reduce the opportunities and incentives for violence. Moving from the idea that territorial control is a function of ethnic polarization, the article posits that peacekeepers are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Their study focuses on the local variation in eastern DRC with regards to the presence (as well as the number and type) of peacekeepers and the occurrence of political violence in the form of fighting and violence against civilians as coded by the EDACS (Chojnacki et al 2012). Although this finding contradicts the work by Costalli (2014), who concludes that UN troops failed to effectively reduce violence during the Bosnian war, it is largely in line with other recent studies of the local effects of peacekeeping (Cil et al 2019;Di Salvatore 2018;Fjelde et al 2019;Phayal 2019;Phayal and Prins 2019;Ruggeri et al 2017). While these have variying ideas about when and how peacekeeping works at the local level, most recent studies have identified a violence-reducing effect of UN peacekeeping.…”
Section: What Do We Know By Now?mentioning
confidence: 52%
“…Their study focuses on the local variation in eastern DRC with regards to the presence (as well as the number and type) of peacekeepers and the occurrence of political violence in the form of fighting and violence against civilians as coded by the EDACS (Chojnacki et al 2012). Although this finding contradicts the work by Costalli (2014), who concludes that UN troops failed to effectively reduce violence during the Bosnian war, it is largely in line with other recent studies of the local effects of peacekeeping (Cil et al 2019;Di Salvatore 2018;Fjelde et al 2019;Phayal 2019;Phayal and Prins 2019;Ruggeri et al 2017). While these have variying ideas about when and how peacekeeping works at the local level, most recent studies have identified a violence-reducing effect of UN peacekeeping.…”
Section: What Do We Know By Now?mentioning
confidence: 52%
“…Di Salvatore (2018) confirms that UN troops reduce civilian deaths. However, she finds that peacekeepers become less effective as the power asymmetries between armed ethnic groups grow.…”
Section: Reducing Civilian and Combatant Killing In Civil Warmentioning
confidence: 83%
“…Do peacekeepers protect by reducing violence against civilians and combatants in the midst of war? To date, more than a dozen quantitative studies have examined the effect of peacekeeping and outside interventions in protecting civilians, and the answer is yes (Costalli 2013;Carnegie and Mikulaschek 2018;Di Salvatore 2018;Fjelde, Hultman and Nilsson 2018;Hultman, Kathman and Shannon 2013;Kathman and Wood 2011;Kathman and Wood 2016;Bove and Ruggeri 2016;Kirschner & Miller 2019;Melander 2009;Phayal 2019;Phayal and Prins 2019). 3 These studies examine somewhat distinct sets of cases and time periods, and measure key variables slightly differently.…”
Section: Reducing Civilian and Combatant Killing In Civil Warmentioning
confidence: 99%
“…While we expect UN PKOs to affect rebels' choice of terrorism in civil wars (as others have also shown, see Hansen et al, 2020), we reiterate the need to consider which factors enable rebels' adaptation. PKOs are not deployed in a vacuum; their effect on belligerents' behaviour is influenced by pre-existing local conditions and by the specific responses of the warring parties to changes brought about by the PKO (Di Salvatore, 2018). Against this background, we develop a theory of rebel groups' heterogeneous responses to PKOs and show how this induces some rebels to escalate terrorist violence.…”
Section: Changes In Strategic Environment and Bargaining Power: When ...mentioning
confidence: 99%